Aplikasi Motif Hias Tinggalan ArkeologiMasa Hindu-Budha Menjadi Motif Hias Batik di Daerah Istimewa Yogyakarta dan Trowulan - Husnun Anggraini, Kinanti (Humanis, 2017)
The archaeological relic in the form of temples, statues, and terracotta have decorative patterns with aesthetic and philosophical value, the decorative patterns can be classified based on media, form, function, and meaning. It is used by the community as an inspiration in making decorative batik patterns. The results obtained in the research on two areasYogyakarta and Trowulan Mojokerto District have found some archaeological ornamental relic patterns applied to decorative batik patterns. The ornamental patterns include: in the Special Region of Yogyakarta there are decorative pattern Kawung or Ceplok, ornamental patterns Kalpataru and Kinara-kinari, while in Trowulan area there are ornamental solar pattern Majapahit, ornamental pattern Padma. There are several factors that become consideration in applying ornamental patterns of archaeological relic into decorative patterns of batik, namely: decorative patterns have aesthetic value, economic value, historical value, and value of science.